Management of Mouth Preparation in Patients with Congenital Heart Disease: Subaortic Ventricular Septal Defect accompanied by Atrial Septal Defect under General Anesthesia: Penatalaksanan Mouth Preparation Pada Pasien dengan Kelainan Jantung Bawaan Ventricular Septal Defect Subaortic disertai Atrial Septal Defect dengan Anestesi Umum - Andini, Rizqi Aulia Kusuma; Daniati, Reni Puspa; Dayanti, Marisa Elvi; Ashari, Tontowi (Indonesian Journal of Innovation Studies, 2025)
General Background: Congenital heart disease (CHD) is a common structural or functional abnormality of the heart and great vessels that increases the risk of infective endocarditis, especially in pediatric patients. Specific Background: Children with complex defects such as subaortic Ventricular Septal Defect (VSD) accompanied by Atrial Septal Defect (ASD) and pulmonary hypertension are particularly vulnerable to oral infections that can lead to systemic complications. Knowledge Gap: Despite the recognized link between oral health and CHD, comprehensive protocols for dental “mouth preparation” under general anesthesia to minimize bacteremia and endocarditis risk before cardiac surgery remain limited. Aims: This case report describes a multidisciplinary approach to full-mouth preparation in a 4.5-year-old boy with VSD subaortic, ASD, and severe pulmonary hypertension, focusing on infection elimination, anesthesia management, and prophylactic strategies. Results: Treatment included restorations with Glass Ionomer Cement for reversible pulpitis, multiple extractions of necrotic teeth under general anesthesia, preoperative laboratory and radiological screening, American Society of Anesthesiologists assessment, and antibiotic prophylaxis with intravenous ampicillin followed by oral amoxicillin. Postoperative recovery was uneventful, with stable vital signs and satisfactory wound healing after one week. Novelty: This report highlights the integrated collaboration of pediatric dentistry, cardiology, and anesthesiology to ensure airway control, hemodynamic stability, and asepsis during extensive dental procedures in high-risk CHD patients. Implications: The findings underscore the importance of rigorous preoperative dental management and continuous preventive care—including parental education, low-sugar diet counseling, and regular dental visits—to reduce long-term risks of caries recurrence and infective endocarditis in children with congenital heart defects. Highlights: Comprehensive dental preparation prevents infective endocarditis risk. Multidisciplinary approach ensures safe anesthesia and hemodynamic stability. Ongoing preventive care reduces caries recurrence and systemic infection. Keywords: congenital heart disease, ventricular septal defect, atrial septal defect, dental management, general anesthesia